Anti-decubitus prophylaxis in nursing practice - Pacholec, Agata (Journal of Education, Health and Sport, 2019)
Long-standing patients are at risk of developing and developing bedsores, and this problem has a significant impact on their physical and mental state. As a result of pressure and friction on tissues, necrosis develops. Bedsores are often the result of inadequate patient care and coexisting diseases. Nursing care does not always prevent the formation of bedsores, but it can significantly affect the degree of their development. In the process of taking care of an immobilized person we should apply the risk assessment of the occurrence of bedsores and on its basis adjust the prevention of bedsores (change of position, use of an anti-decubitus mattress or careful care of the skin). The most common places for the development of decubitus ulcers are the areas of bone elevation exposed to friction and pressure. The aim of this study is to show the importance of appropriate prevention, care and treatment in the care of a patient who has been lying down for a long time. The paper is based mainly on a review of articles in reputable journals from the last few years.